2013
DOI: 10.2217/nnm.12.95
|View full text |Cite|
|
Sign up to set email alerts
|

Metallofullerol Nanoparticles with Low Toxicity Inhibit Tumor Growth by Induction of G0/G1 Arrest

Abstract: Results further demonstrated that [Gd@C(82)(OH)(22)](n) could inhibit tumor growth by inducing tumor cell and vein endothelial cell G0/G1 arrest, which may explain the low toxicity of [Gd@C(82)(OH)(22)](n).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(6 citation statements)
references
References 163 publications
(338 reference statements)
0
6
0
Order By: Relevance
“…1). 25 G1 is the initial phase of the cell cycle. In this stage, cells must acquire all necessary information to proceed safely into the S phase.…”
Section: Cell Cycle Regulation By [Gd@c 82 (Oh) 22 ] N Nanoparticlesmentioning
confidence: 99%
“…1). 25 G1 is the initial phase of the cell cycle. In this stage, cells must acquire all necessary information to proceed safely into the S phase.…”
Section: Cell Cycle Regulation By [Gd@c 82 (Oh) 22 ] N Nanoparticlesmentioning
confidence: 99%
“…The Gd@C 82 (OH) 22 derivative was reported to have reduced the density of tumor micro-vessels by suppressing the angiogenesis (Kang et al 2012 ) and has even shown inhibition of oxidative stress in the hepatocells (Wang et al 2006 ). Various studies have shown that this fullerene derivative also acts by cell cycle regulation arresting the G0 phase (Meng et al 2013 ) and that they inhibit MMP-2 and MMP-9 with high anti-tumor activity (Meng et al 2012 ).…”
Section: Fullerenes In the Diagnosis And Treatment Of Tumorsmentioning
confidence: 99%
“…The growth of tumor cell could also be inhibited by [Gd@C 82 (OH) 22 ] n NPs by regulating the cell cycle,, which may explain the low toxicity of nanoparticles. Zhao Y et al reported that [Gd@C 82 (OH) 22 ] n inhibits both MCF-7 and ECV304 cell growth by inducing the G0/G1 phase arrest [ 11 , 12 ]. [Gd@C 82 (OH) 22 ] n naturally prevent the entry of cells into the S phase and induce cell apoptosis by down-regulated expression of CDK4, CDK6, cyclinE, cyclinD2 and Bcl-2 and by up-regulated expression of P21 and Bax [ 12 ].…”
Section: Fullerene Derivatives: Promising New Anti-tumor Nanoparticlesmentioning
confidence: 99%
“…20 cellular immunity activation T lymphocytes and macrophages/C57BL/6 mice improve the immune response to kill tumor cells. [3] tumor metastasis inhibition EMT-6 breast cancer metastasis model inhibit tumor cell proliferation [4] Gd@C 82 (OH) 22 cellular immunity activation dendritic cells and macrophages /C57BL/6 activate Th1 Immune Responses [5,6] angiogenesis suppression malignant human breast cancer models/cancer stem cells reduce tumor microvessels density (MVD) [7][8][9] inhibition of oxidative stress hepatoma cell normalize the activity of enzymes related to oxidative stress [10] cell cycle regulation MCF-7 and ECV304 cell induce the G0/G1 phase arrest [11,12] tumor metastasis inhibition BALB/c nu/nu female mice inhibit MMP-2 and MMP-9 with high antitumoral efficacy [13] C 60 (OH) 24 inhibition of oxidative stress A549 cells attenuate oxidative stress-induced apoptosis [14] Gd@C 82 -(EDA) 8 maintain a reactive oxygen species (ROS) balance human epidermal keratinocytes-adult scavenge hydroxyl radicals [15] β-alanine modified gadofullerene nanoparticles (GFNPs) tumor photodynamic therapy melanoma cancer cells/female BALB/c nude mice disrupt tumor vasculatures [16] C 60 -Cisplatin nanocomplexs drug delivery carriers lewis lung carcinoma cells enhance the toxic effect of cisplatin on lung cancer cells [17] C 60 -Berberiner nanocomplexes CCRF-CEM cells inhibit the proliferation of CCRF-CEM cells [18] Fullerenes can be modified by carbon cage internal nesting and carbon cage surface modification. On the one hand, the hollow interior of the carbon cage can contain single atoms, clusters of atoms and even small molecules [19,20].…”
Section: Introductionmentioning
confidence: 99%